Effect Contact Time Adsorption of Naphtol Dye Using Humic Acid Adsorbent Result of Peat Isolation from Kalimantan - Prandini, Masyithah Nisvi; Rahmayanti, Maya (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Adsorption of naphtol dye was carried out by using humic acid adsorbent from the isolation of Kalimantan peat. This study aims to determine the effect of the adsorption contact time on humic acid naphtol dyes from Kalimantan peat isolation. The purified humic acid isolation was characterized using Fourier Transform Infra-Red (FTIR), Scanning Electron Microscopy (SEM), Optical Microscopy, total acidity measurement, and measurement of -COOH (carboxylate) and -phenol OH groups. The characterized humic acid was then used as an adsorbent to adsorb the naphthol dye solution. The adsorption process was measured using a UV-Vis spectrophotometer to determine the concentration of adsorbed naphthol dye. The adsorption study of the research results showed that the optimum adsorption time of naphthol dye to humic acid was 45 minutes, this was because almost all naphtol dyes were adsorbed on humic acid.